Perlindungan Hukum terhadap Pemberian Hak Nafkah Anak Pasca Perceraian - Vina Rosalinda; Sabar Podu; Amri Amri (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
Child support rights after divorce constitute a fundamental right that must be protected to ensure children's welfare and development. However, many children do not receive adequate financial support because parents, particularly fathers, fail to fulfill their obligations after divorce. This study aims to analyze the legal regulation of child support rights after divorce and examine the legal protection available when these rights are neglected. The research employs normative legal research using statutory and conceptual approaches. Legal materials were collected through library research, including legislation, legal literature, scholarly journals, and relevant court decisions. The findings show that Indonesian law provides a comprehensive legal framework through the Marriage Law, the Child Protection Law, and the Compilation of Islamic Law, all of which affirm that divorce does not terminate parental responsibilities. Under Islamic law, the obligation to provide child support remains with the father. Legal protection is available through civil and criminal mechanisms, including enforcement claims and criminal liability for child abandonment. However, weak law enforcement, limited supervision of court decisions, and low legal awareness continue to hinder effective protection. Strengthening enforcement, increasing legal awareness, and enhancing state involvement are essential to ensure the fulfillment of child support rights after divorce.